(untitled) (Foro de Educacion, 2016)
Economic, politics and communication globalization is one of the main problems of the present historical reality that undermines social identities based on membership in local communities and well-defined. The transformations of social, cultural and economic related globalization corresponds to a complexity and multidimensionality of the concept of citizenship. Today the term citizenship does not longer refers exclusively to participation in public life and membership in a nation-state. The different concepts of citizenship have in common the public participation, but nowadays new meanings are accepted. Citizenship doesn’t mean anymore belonging to a Nation but cultural and ethical reasons broaden that concept to include the universal human rights. We need to make in order to restrict in terms of pedagogic elements of educational experience that can be understood within the context of citizenship education in and outside school.